عمدۃ البیان فی تفسیر القرآن میں کلامی مباحث کا تجزیاتی مطالعہ: Dialectical matters In Tafseer Umda tul Bayan: an Analytical Study - Muhammad Imran (MEI, 2023)
Maulana Muhammad Ishaq Khan al-madani gave due place to the dialectical matters in his exegesis: “Umdatul Bayan fi Tafsir al-Quran”. All the three kinds of dialectical matters e.g. Theologies, prophesies and acoustics are discussed in the exegesis. Keeping the differences of sects of subcontinent in view, his main focus in the interpretation of the Holy Qur‘an is on the reformation of beliefs based on the different exegeses of the Holy Quran .He insisted upon the oneness of Allah Almighty and the characteristics of the oneness of Allah Almighty in his exegesis and he specified them only for Allah Almighty while negating them for Allah Almighty. Furthermore, while discussing the beliefs, he used easy language which is understood by a common man as well. According to him it is necessary that a Tafsir is to be written in a language that is fit to the modern era and that provide satisfactory answers to the errors created by the innovators in the Islamic beliefs. Many of such errors are pointed out and resolved with great concern. In the current article, an attempt has been made to explore the methodology adopted by him in his Tafsir: “‘ Umdatul Bayan fi Tafsir al-Qur‘an” regarding dialectical matters with the analysis of examples.